Viability of dried filaments, survivability and reproduction under water stress, and survivability following heat and UV exposure in Lyngbya martensiana, Oscillatoria agardhii, Nostoc calcicola, Hormidium fluitans, Spirogyra sp. and Vaucheria geminata - Agrawal, S C; Singh, V (Folia microbiologica, 2002)
Dried vegetative filaments of Spirogyra sp., Vaucheria geminata and Nostoc calcicola died within 1/2, 1 and 4 h, respectively; those of Hormidium fluitans, Oscillatoria agardhii and Lyngbya martensiana retained under similar storage conditions viability for 3, 5 and 10 d, respectively. The viability of dried vegetative filaments of L. martensiana, O. agardhii and H. fluitans decreased on storage at 20 degrees C in the dark. L. martensiana and O. agardhii tolerated 0.8 mol/L NaCl. The resistance to desiccation in L. martensiana and O. agardhii exhibited similar dependence as that to frost, to heat and UV light. O. agardhii filaments became slightly broader and their cells developed large number of gas vacuoles when grown in 0.8 mol/L NaCl-containing medium. The water stress imposed on growing algae either on high-agar solid media or in NaCl-containing liquid media reduced hormogonium formation in L. martensiana and O. agardhii, heterocyst and akinete formation in N. calcicola and fragmentation in H. fluitans; it did not induce conjugation in Spirogyra sp. and formation of reproductive organs in V. geminata. In all studied algae the stress reduced at various levels the survival of vegetative parts. Generally, algal body form and composition rather than habitats seem to decide primarily the level of resistance against various stress conditions.
Keywords: chlorid sodný; Reproduction; Hot Temperature; reakce na tepelný šok; Cyanobacteria; rozmnožování; Sodium Chloride; Heat-Shock Response; sinice; kultivační média; Ultraviolet Rays; vysoká teplota; Culture Media; ultrafialové záření